The trench : MEG 2 - Alten, Steve (Alten, Steve. MEG., 2023)
"On the other side of the world, in the silent depths of the ocean, lies the Mariana Trench, where the Megalodon has spawned since the dawn of time. Paleobiologist Jonas Taylor once dared to enter this perilous cavern. He alone faced a Megalodon shark and cut its heart out. Now, as the body count rises and the horror of a monster's attack grips the California coast, Jonas must begin the hunt again and face his deepest fears--all in order to save his job, his family, and himself." -- Amazon.